Economic Effectiveness of Tokens in Improving Eating Patterns in Mental Retardation Children - Mayang Safitri Aswina; Pratikto Herlan (Proceedings of The ICECRS, 2020)
Mental retardation is one factor that affects the lack of cognitive abilities of individuals in learning and understanding learning or understanding commands given. People with mental retadation needs more help in learning, repetition, and double attention than childs at their age. This research method was qualitative, the type was single-subject experiment, and the client was a 9.3-year-old girl with an IQ of 64. The data collection used by researchers in this study was the interview method (autoanamnesa and alloanamnesa), observing the subject's behavior at home, when she was playing and learning. The psychological tests given are CPM, Bender Gestalt, and Graphics (BAUM, DAP, HTP). An economic token as the type of intervention used, tried to help improve the eating patterns of subjects who were previously less organized. The token used in the form of color paper was affixed to the subject's daily journal if it has performed the assigned task. The intervention was carried out within 14 (fourteen) days, divided into two sessions. Calculation of total tokens to got the reward in a week, and the minimum value is eighteen tokens, and prizes agreed upon in the form of a large picture book. The results showed a change in client behavior from before and after the intervention given.